2014
DOI: 10.1097/qai.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

Immune Activation Is Associated With Increased Gut Microbial Translocation in Treatment-Naive, HIV-Infected Children in a Resource-Limited Setting

Abstract: Background Gut damage resulting in microbial translocation (MT) is considered a major cause of immune activation (IA) in HIV infection, but data in children are limited, particularly in the absence of antiretroviral therapy. Methods Sixty perinatally HIV-infected, antiretroviral therapy–naive children, aged 2–12 years, were evaluated for plasma levels of lipopolysaccharide, DNA sequences encoding bacterial ribosomal 16 second (16S) RNA (16S rDNA) and soluble CD14 concurrently with markers of CD4 and CD8 T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
18
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 50 publications
4
18
1
Order By: Relevance
“…This has been observed in HIV-infected adults [10]. Our results support previous observations that HIV-infected children have gut-associated lymphoid tissue injury resulting in persistent microbial translocation and/or defects in LPS clearance mechanisms [11][12][13]15,16].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…This has been observed in HIV-infected adults [10]. Our results support previous observations that HIV-infected children have gut-associated lymphoid tissue injury resulting in persistent microbial translocation and/or defects in LPS clearance mechanisms [11][12][13]15,16].…”
supporting
confidence: 91%
“…During the acute phase of infection, the main driver of immune activation appears to be high levels of virus with other factors such as microbial translocation more important in chronic infection [8]. Few studies have focused on immune activation and microbial translocation profiles of HIVinfected children [11][12][13].…”
mentioning
confidence: 98%
“…We saw this effect both in unstimulated monocytes and in cells activated with two stimuli implicated in HAND pathogenesis, LPS and MCP-1. Residual inflammation in ART-treated individuals, believed to be a major contributor to HAND (Yadav and Collman 2009; Chen, Gill et al 2014), is partially driven by persistent translocation of microbial products such as LPS, due to incomplete restoration of damaged gut immune barrier (Jiang, Lederman et al 2009; Pilakka-Kanthikeel, Kris et al 2014). Similarly, MCP-1 is elevated in HIV infection and, in particular, recruits monocytes to tissues (Williams, Calderon et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, data suggest that IE could be critical in the viral persistence that characterizes chronic HIV infection [28]. To date, few studies have investigated IE in HIV-infected children [18, 23]. These studies both demonstrated an increase in IE compared to healthy controls, but only ART-naïve children were included.…”
Section: Introductionmentioning
confidence: 99%